Answer:
Explanation:
a) -14 , -9 , -4 , 1 ................
Common difference = d = 2nd term - 1st term
= -9-[-14]
= -9 + 14
d = 5
The next term can be got by adding 5 to the previous term
5th term = 1 + 5 = 6
6th term = 6 + 5 = 11
7th term = 11 + 5 = 16
Next 3 terms are : 6 , 11 , 16
![b) (5)/(6),(2)/(3),(1)/(2),(1)/(3),.....\\\\d = (2)/(3)-(5)/(6)\\\\=(2*2)/(3*2)-(5)/(6)\\\\=(4)/(6)-(5)/(6)\\\\=(-1)/(6)\\\\a_(5) = (1)/(3)+(-1)/(6)=(1*2)/(3*2)+(-1)/(6)=(2)/(6)+(-1)/(6)=(1)/(6)\\\\a_(6)=(1)/(6)+(-1)/(6)=0\\\\a_(7)=0+(-1)/(6)=(-1)/(6)\\\\\\Next 3 terms : (1)/(6),0,(-1)/(6)](https://img.qammunity.org/2022/formulas/mathematics/high-school/7dy05jo7quw3vt1udog6vdme17k9ywn1ux.png)